2016
DOI: 10.12659/msm.897639
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Pedicle Screw Fixation with Bone Graft vs. Bilateral Pedicle Screw Fixation with Bone Graft or Cage: A Comparative Study

Abstract: BackgroundThe aim of this study was to explore the clinical efficacy of unilateral pedicle screw fixation with bone graft (UPSFB) in treating single-segment lumbar degenerative diseases (LDD), as compared to bilateral pedicle screw fixation with bone graft (BPSFB) or with cage (BPSFC).Material/MethodsMedical records were retrospectively collected between 01/2010 and 02/2015 in Longyao County Hospital. According to surgical methods used, all patients were divided into 3 groups: UPSFB group, BPSFB group, and BPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The use of bilateral PS fixation is associated with another drawback which is more blood loss, since it is inevitable to have more blood loss during neural elements decompression along with screws application on both sides. This is a clear-cut fact reported in all studies [2,8,19,23,24].…”
Section: Clinical Outcomessupporting
confidence: 51%
See 2 more Smart Citations
“…The use of bilateral PS fixation is associated with another drawback which is more blood loss, since it is inevitable to have more blood loss during neural elements decompression along with screws application on both sides. This is a clear-cut fact reported in all studies [2,8,19,23,24].…”
Section: Clinical Outcomessupporting
confidence: 51%
“…Intraoperative complications included unintended durotomy that took place in three patients, two in the bilateral group and a single case in the unilateral group, where the dural tear was repaired intraoperatively via dural sutures augmented by a fat graft and no lumbar drain was required. Yang et al [24] reported also three cases to have a dural tear, again one in unilateral group and two in bilateral group. All were managed conservatively as well with no occurrence of any further complications.…”
Section: Clinical Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…Subsidence of bone graft and decline in bone mineral cause a decrease in fusion rates. (6,12,18,25,(39)(40)(41). Likewise, it is reported in the literature that unilateral pedicle fixation with the TLIF procedure has many advantages compared to bilateral PSF.…”
mentioning
confidence: 99%
“…Both a posterior screw-rod fixation system and solid intervertebral cages were selected for the PLIF surgery [4,5].…”
Section: Introductionmentioning
confidence: 99%